2023
DOI: 10.3389/fimmu.2023.1102530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Abi3 locus deletion on the progression of Alzheimer’s disease-related pathologies

Abstract: Human genetics studies of Alzheimer’s disease (AD) have identified the ABI3 gene as a candidate risk gene for AD. Because ABI3 is highly expressed in microglia, the brain’s immune cells, it was suggested that ABI3 might impact AD pathogenesis by regulating the immune response. Recent studies suggest that microglia have multifaceted roles in AD. Their immune response and phagocytosis functions can have beneficial effects in the early stages of AD by clearing up amyloid-beta (Aβ) plaques. However, they can be ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Notably, our results distinctly discovered a CTS cis-eQTL, rs78366152, for AP3B2 , an AD risk gene interrogated in multiple mouse model studies 32,33 ( Figure 5B ). In our eQTL meta-analysis results, this gene-variant pair is significant in microglia, oligodendrocyte, and astrocyte, but not in excitatory neuron.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Notably, our results distinctly discovered a CTS cis-eQTL, rs78366152, for AP3B2 , an AD risk gene interrogated in multiple mouse model studies 32,33 ( Figure 5B ). In our eQTL meta-analysis results, this gene-variant pair is significant in microglia, oligodendrocyte, and astrocyte, but not in excitatory neuron.…”
Section: Resultsmentioning
confidence: 69%
“…We found that 23.4% and 14.7% of cis-eQTL gene-variant pairs exclusively identified by us were also significant in these two datasets respectively, while only 6.5% and 4.8% of exclusive microglia eQTLs from Bryois et al can be replicated by the two microglia eQTL studies. Notably, our results distinctly discovered a CTS cis-eQTL, rs78366152, for AP3B2, an AD risk gene interrogated in multiple mouse model studies 32,33 (Figure 5B). In our eQTL meta-analysis results, this gene-variant pair is significant in microglia, oligodendrocyte, and astrocyte, but not in excitatory neuron.…”
Section: Epic-unmix Boosts Power For Downstream Cts Differential Expr...mentioning
confidence: 71%